Tanggung Jawab Perdata Dokter Spesialis Terhadap Kerugian Pasien Akibat Kesalahan Diagnosis - Yeni Vitrianingsih (Journal of Indonesian Comparative of Syari'ah Law, 2023)
Civil liability of specialist doctors for patient losses due to misdiagnosis. Background between specialist doctors and patients is based on therapeutic transactions (artsenovereenkomst), engagement (inspanningsverbintenis), engagement (resultaatverbintenis). Specialist doctors are required to have a higher level of skill and accuracy (standard of care) than general practitioners. Misdiagnosis that occurs due to negligence or carelessness of specialist doctors can trigger physical, material, and immaterial losses to patients, resulting in medical disputes. The first research objective is to analyze the legal qualifications of specialist doctors' misdiagnosis categorized as a violation of civil law. Second, to examine the form of civil liability. The research method in this study uses a normative juridical approach with descriptive-analytical research specifications. The data used are secondary data consisting of primary legal materials (Civil Code, Health Law), secondary legal materials. Data analysis was conducted qualitatively. The results of the study show that the legal qualifications of specialist doctors' misdiagnosis do not necessarily constitute legal responsibility if they comply with Standard Operating Procedures (SOP) and Medical Service Standards (SPM). Such errors arise from gross negligence or a violation of professional standards. They can be classified as breach of contract (Article 1243 of the Civil Code) if they violate the contractual clauses, or more commonly, as unlawful acts (Articles 1365 & 1366 of the Civil Code) if there is evidence of fault, loss, and a causal relationship (causaliteit). Furthermore, in terms of liability, specialist doctors are held personally liable or jointly liable with the hospital based on the doctrine of vicarious liability (Article 1367 of the Civil Code).